An Integrative Model of Workplace Self-protective Behavior for Korean Nurses - Seol Ah Kim, MSN, RN; Hyun Soo Oh, PhD, RN; Yeon Ok Suh, PhD, RN; Wha Sook Seo, PhD, RN (Elsevier, 2014)
Purpose: This study was conducted to develop and test a hypothetical stage model of workplace self-protective behaviors with respect to blood transmitted infections and musculoskeletal injuries for Korean nurses. Methods: A nonexperimental, cross-sectional study design was adopted. The study participants were 320 nurses at two Korean university hospitals. Perceived sensitivity, severity, barriers, benefits, self-efficacy, social support, and safety climate were assessed. Results: Overall, fit indicators showed a good fit for the hypothetical model of self-protective behaviors against blood transmitted infections and musculoskeletal injuries. The significant factors of self-protective behaviors against blood transmitted infections were perceived barriers and social support. The significant factors of self-protective behaviors against musculoskeletal injuries were perceived benefits, barriers, and self-efficacy. Conclusion: Our findings suggest that the significant psychosocial constructs of stages of self-protective behavior are dependent on health problem type. Accordingly, we advise that characteristics of behavior and types of disease and health problem should be given priority when developing intervention programs for particular self-protective health behaviors.